Peer-to-Peer Crowdfunding: Information and the Potential for Disruption in Consumer Lending - Morse, Adair (Annual review of financial economics)
Can peer-to-peer lending (P2P) disintermediate and mitigate information frictions in lending so that choices and outcomes for at least some borrowers and investors are improved? I offer a framing of issues and survey the nascent literature on P2P. On the investor side, P2P disintermediates an asset class of consumer loans, and investors may be able to capture rents associated with the removal of a layer of financial intermediation. Risk and portfolio choice questions linger prior to any inference. On the borrower side, evidence suggests that proximate knowledge (direct or inferred) unearths soft information. Thus, P2P may be able to offer pricing and or access benefits to potential borrowers. Early research suggests that the future of consumer lending will involve more big data and reintermediation of underwriting by all types of financial institutions. I ask many more questions than current research can answer, hoping to motivate future research.